Perawatan Paliatif Berbasis Rumah pada Pasien Gagal Jantung Kongestif: Studi Literatur - Wattimena, Christy; A. Alves, Sebastiao; Rayu ID, Anisa (Journal of Pubnursing Sciences, 2024)
Background: Heart failure is one of the diseases whose condition is difficult to predict, the cost of follow-up treatment is expensive and there is no certainty of the results of the therapy given. Some previous studies have suggested that home-based palliative care in heart failure patients can help the healing process and reduce health care costs. Aims: to explore home-based palliative care for patients with heart failure. Method: Literature reviews are conducted with systematic searches across multiple databases–Science Direct, Google Scholar and PubMed (2016 to 2023). Studies are selected based on the content of home-based palliative care programs and their impact evaluation. Results: Eleven full articles that met the inclusion and exclusion criteria were examined. Seven articles did not clearly and specifically discuss home-based palliative care in heart failure patients so the remaining 4 articles discussed in this literature review. All articles focused on home-based palliative care in patients with heart failure. Conclusion: Home-based palliative care implemented by multidisciplinary teams, can reduce the utilization of health services and health care costs, reduce readmisi, improve symptom control, improve quality of life, increase satisfaction with care and lower caregiver burden on heart failure patients.